Pengembangan Media Ular Tangga dalam Bimbingan Kelompok untuk Meningkatkan Perencanaan Karier - Irfan Irfan; Jarkawi Jarkawi; Eka Sri Handayani (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2020)
The research aims: To find out how the development of snake and ladder media in group guidance to improve guidance services in the career field towards career planning for students of SMAIT Ukhuwah Banjarmasin. This study used the research and development method, from 10 stages the researcher used 5 stages to adjust the research needs with the following steps: (1) Potential and problems. (2) Data collection. (3) Product design. (4) Design validation. (5) Design improvements. This research is motivated by the process of providing guidance services in the field of career planning which still uses conventional old media (power point) which causes service delivery to be less than optimal and has never used any new media. The results of this study indicate that the medium of snake and ladder in group guidance to improve guidance services in the career field of career planning for students of SMA Islam Terpadu Ukhuwah Banjarmasin is feasible and usable. This can be seen from the results of the media validation assessed by counseling teacher practitioners by giving an assessment between 81.0% - 100.0% which means very valid, can be used without revision. Keywords: Old Media, Snake and Ladder Media, Career Planning